Prof. Ahmad Fawad an Anti Traditional Poet - Aziz, Tariq; Iqbal, Sidiq; Altaf Yousafzai, Muhammad (sourcecoder, 2022)
Ahmad Fawad is a professor in English. He has already published three combinations of Urdu poetry. He is the Mir-e-karwan of the Urdu poets of swat. His poetry is an example of indecency and Narrative. I have not restricted myself, but have taken my imagination flight to the house. The fascinating and ethical system of Ahmad Fawad poetry is not based on poetic dramatism, but these symbols are apparently simple but their original, third Darwinists are immersive and universal. Their rhythm’s poetry and successful experience , their physical power and subordinate order. Creative sign of deviation from the new linguistic argument in his poetry.His unique style of comfort makes him different from other poets.